Antifogging Surface Facilitated by Nanoscale Coatings with Controllable Hydrophobicity and Cross‐Linking Density. Issue 1 (1st August 2016) - Nam, Eunhyung; Wong, Edgar H. H.; Tan, Shereen; Fu, Qiang; Blencowe, Anton; Qiao, Greg G.
Abstract : Surface confined and cross‐linked poly(ethylene glycol)‐based films with great antifogging function are fabricated via catalyst induced cross‐linking, which is an efficient methodology to produce films with controllable properties including thickness, cross‐linking density, and swellability. Using the produced films under changes in environmental conditions, the crucial role of film cross‐linking density and hydrophilicity on the antifogging function is demonstrated. Abstract : Antifogging and frost‐resistant coatings can be used in a wide range of applications and enable high light transmission through substrates even under changes in environmental conditions. In this study, surface confined and cross‐linked antifogging thin films are fabricated on glass slides via catalyst induced cross‐linking (CIC), which has been recently introduced as an easy and efficient cross‐linking methodology. Four different poly(ethylene glycol) (PEG)‐based polymers with different hydrophilicity are synthesized and used to prepare films via CIC. Films prepared from the most hydrophilic PEG‐based polymers display the best antifogging performances when exposed to a temperature change from −20 to 22 °C. Furthermore, several parameters including cross‐linking density, surface roughness, hydrophobicity, and exposure time are also evaluated in terms of film transparency. Through these measurements, it is determined that, more loosely cross‐linked films retain antifogging ability for longer time periods due to higher film swellability as compared to, more highly cross‐linked films. This study signifies the crucial role of the film cross‐linking density and hydrophilicity on the antifogging function.